A hybrid stochastic fractional order Coronavirus (2019-nCov) mathematical model. (April 2021) - Sweilam, N.H.; AL - Mekhlafi, S.M.; Baleanu, D.
Highlights: A new stochastic fractional Coronavirus (2019-nCov) mathematical model with modified parameters are presented. Milstein's higher order method is constructed to study the model problem Mean square stability of Milstein algorithm is proved. Comparative studies and numerical simulations are implemented Abstract: In this paper, a new stochastic fractional Coronavirus (2019-nCov) model with modified parameters is presented. The proposed stochastic COVID-19 model describes well the real data of daily confirmed cases in Wuhan. Moreover, a novel fractional order operator is introduced, it is a linear combination of Caputo's fractional derivative and Riemann-Liouville integral. Milstein's higher order method is constructed with the new fractional order operator to study the model problem. The mean square stability of Milstein algorithm is proved. Numerical results and comparative studies are introduced.